2016
DOI: 10.1038/gim.2015.107
|View full text |Cite
|
Sign up to set email alerts
|

A critical reappraisal of dietary practices in methylmalonic acidemia raises concerns about the safety of medical foods. Part 2: cobalamin C deficiency

Abstract: PURPOSE Cobalamin C (cblC) deficiency impairs the biosynthesis of adenosyl- and methylcobalamin resulting in methylmalonic acidemia combined with hyperhomocysteinemia and hypomethioninemia. However, some patients with cblC deficiency are treated with medical foods, devoid of methionine and high in leucine content, that are formulated for patients with isolated propionate oxidative defects. We examined the effects of imbalanced branched-chain amino acid intake on growth outcomes in cblC patients. METHODS Diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 46 publications
1
42
1
2
Order By: Relevance
“…The high frequency of the c.482G>A(p.Arg161Gln) pathogenic variant in our cohort contributes to this observation as 13/27 (48%) of our individuals are compound heterozygous for this variant compared to 4/86 (5%) individuals in these published studies (combined) 8, 9, 1418 .…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…The high frequency of the c.482G>A(p.Arg161Gln) pathogenic variant in our cohort contributes to this observation as 13/27 (48%) of our individuals are compound heterozygous for this variant compared to 4/86 (5%) individuals in these published studies (combined) 8, 9, 1418 .…”
Section: Resultsmentioning
confidence: 55%
“…Other agents like betaine, folic acid, and carnitine may also be prescribed. A special diet, including protein restriction, is not necessary and not recommended 8,9 . The long term outlook of cobalamin C disease in the era of newborn screening is yet to be comprehensively explored.…”
Section: Introductionmentioning
confidence: 99%
“…Patients on protein-restricted diets had lower height-for-age z-score. Patients consuming medical foods with presumably low Met supply had lower head circumference and lower plasma Met concentrations (Manoli et al 2015). For these reasons, methionine-free formulas and protein restriction leading to low methionine plasma levels is contraindicated in cblC patients (Ogier de Baulny et al 1998; Manoli et al 2015).…”
Section: The Effects Of Treatment On Clinical Outcomementioning
confidence: 99%
“…Although patients with cblC were traditionally restricted in protein intake, in a recent survey, none of 88 European patients received protein restriction (Fischer et al 2014). Furthermore, recent studies of treatment in cblC found no benefit in restricting protein access and a possibly deleterious effect of using low-methionine medical foods (Manoli et al 2015). Hyperhomocystinuria is a known risk factor for thrombosis.…”
Section: Pathophysiology Molecular Analyses and Treatment In Relatimentioning
confidence: 99%